Intergenerational Analysis of Educated Unemployment Duration in East Java: A Multilevel Survival Approach Toward School-to-Work Transition Policies - Barsua, Ni Putu Esti Utami; I Ketut Adi Chandra Wiguna; Ikhlasul A’mal; Muhammad Dokhi (Pusat Pengembangan Kebijakan Ketenagakerjaan Kementerian Ketenagakerjaan Republik Indonesia, 2025)
Educated unemployment, particularly among Generation Z (Gen Z), poses a major challenge to inclusive and sustainable labor market development. East Java, as a province with a large population and a high proportion of young people, exhibits a pronounced trend of unemployment among Gen Z in both rate and duration. This study employs a multilevel survival analysis using the 2023 National Labor Force Survey (Sakernas) to compare the unemployment duration between Gen Z and Gen XY (a combination of Generations X and Y) and to identify the factors influencing it. The results reveal that Gen Z experiences longer unemployment durations and responds less effectively to formal interventions such as job training and the Prakerja program. Conversely, factors such as age, marital status, and education level significantly affect both groups. Income inequality, measured by the gini ratio, tends to prolong unemployment, while dynamic labor market conditions—reflected in higher labor force participation rates and regional GDP—help accelerate the transition to employment. Based on these findings, this study proposes the JAWARA KERJA program (East Java Initiative for Labor Market Access and Resilience), which emphasizes adaptive training for Gen Z, skill enhancement for Gen XY, and integration of labor market information systems. This program is expected to serve as a targeted and responsive policy for improving the school-to-work transition and addressing intergenerational disparities in the regional labor market.